The effect of road and air transport infrastructure on FDI Inflows in MENA countries: A panel data analysis - Bensoltane BASSEM (Transport Economics and Management)
The relationship between transport infrastructure and Foreign Direct Investment (FDI) has been, and remains, a critical area of research. Accordingly, this study investigates their interplay in 15 MENA countries from 1996 to 2022, using panel data and Ordinary Least Squares (OLS) regression analysis. The results indicate that road transport infrastructure is the most influential factor in attracting FDI, with improvements significantly boosting foreign investment. Similarly, air transport infrastructure contributes positively by enhancing access to global markets, further driving FDI inflows. In contrast, human capital shows no statistically significant effect, while trade openness emerges as a crucial determinant, with liberalized trade policies fostering greater FDI. Exchange rate demonstrates a marginally positive effect, reducing investor uncertainty, whereas market size, measured by GDP per capita, strongly attracts FDI due to larger growth potential and higher purchasing power. Additionally, political stability fosters investor confidence, further supporting FDI inflows. Finally, the interaction effects reveal that road transport infrastructure amplifies the positive impacts of both trade openness and exchange rate on FDI. Building on these findings, the study provides actionable policy recommendations to enhance FDI inflows in the MENA region and highlights promising avenues for future research.